Kajian Teologis Antropologis Terhadap Pemali Dalam Ritual Rampanan kapa' di Toraja - Sarapang, Desna Rura (Jurnal Teologi Kontekstual Indonesia, 2023)
This paper analyzes the Anthropological Theological Study of The Pemali in The Rituals of rampanan kapa’ in Tandung La’bo”, Sanggalangi District, North Toraja . This study uses a qualitative method, where data and facts are obtained directly by using interview techniques, observation, and library studies. The result found five cultures of the pemali in the rituals of rampanan kapa’;1). Pemali sounds a drum where there is a family above the house/family who died; 2). Pemali determines the day either or sees the moon (cannot get married in february/month of sipi’; 3). Pemali unteka’ palanduannatau (no one servant marriied to nobles); 4). Pemali ma’pangngan buni (have affair) and; 5). Pemali urromok busian dirangkan (commit adultery). Through the anthropological study the existence of the pemali in the rituals of rampanan kapa’ is a result of wise thoughts that are lowered by God to the human being to bring a good for the lives of society. Pemali in the rituals of the rampanan kapa’ doesn’t affect the beliefs of the community (Christians)because they are interpreted according to the word of God.